Likuiditas, leverage, profitabilitas dan ukuran perusahaan sebagai predictor agresivitas pajak (Studi Empiris Perusahaan Manufaktur Subsektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2018) - Andi Kartika; Ida Nurhayati (Al Tijarah, 2020)
This study aimed to examine the effect of liquidity, leverage, profitability, and size of firm against tax aggressiveness. Population taken as object observation 176 the consumer goods industry data sector companies listed in Indonesia Stock Exchange in the 2015-2018 period. Determination of sample was made by applying purposive sampling method. The sample used was 98 the consumer goods industry sector companies. Analysis of data used is multiple regression. The result showed that the liquidity had negative influence on tax aggressiveness, the leverage had negative influence on tax aggressiveness, the profitability had positive influence on tax aggressiveness, and size of firm had negative influence on tax aggressiveness.